Policies versus Practice: “Grey” Areas and “Organized Chaos” in Emergency Response - Shawn Jolemore; Nancy Taber (Adult Education Research Conference, 2007)
Paramedics and firefighters work in unpredictable and often dangerous situations. Organizational policies can help in guiding their decision making processes, but learning in practice and relying on experience is most helpful in their daily work. This paper explores how paramedics and firefighters learn to understand their practice through legitimate peripheral participation.